2015
DOI: 10.1124/dmd.114.061317
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Hepatocyte-Kupffer Cell Coculture Model for Assessment of Proinflammatory Cytokine Effects on Metabolizing Enzymes and Drug Transporters

Abstract: Elevated levels of proinflammatory cytokines associated with infection and inflammation can modulate cytochrome P450 enzymes, leading to potential disease-drug interactions and altered small-molecule drug disposition. We established a human-derived hepatocyte-Kupffer cell (Hep:KC) coculture model to assess the indirect cytokine impact on hepatocytes through stimulation of KC-mediated cytokine release and compared this model with hepatocytes alone. Characterization of Hep:KC cocultures showed an inflammation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 28 publications
2
111
1
1
Order By: Relevance
“…In contrast with these findings and in agreement with published data, Il1r1 mRNA was expressed at similar levels in isolated hepatocytes as in total liver (Fig. 3E) (29,30). Furthermore, total liver Il1r1 mRNA levels remained constant at different ages (Fig.…”
Section: Tt/alum/il-36b Induce a Cytokine Storm In Neonatal Micecontrasting
confidence: 55%
“…In contrast with these findings and in agreement with published data, Il1r1 mRNA was expressed at similar levels in isolated hepatocytes as in total liver (Fig. 3E) (29,30). Furthermore, total liver Il1r1 mRNA levels remained constant at different ages (Fig.…”
Section: Tt/alum/il-36b Induce a Cytokine Storm In Neonatal Micecontrasting
confidence: 55%
“…Incorporation of liver stromal cells in MPCCs may allow prediction of drug clearance rates under disease states such as fibrosis and inflammation (Nguyen et al, 2015). Furthermore, miniaturization into a 384-well format should enable higher throughput screening in MPCCs.…”
Section: Discussionmentioning
confidence: 99%
“…KCs were included to build a more complete hepatic cellular microenvironment, and numerous studies have shown their impact on the behavior of in vitro liver systems, such as enhanced IL-1b-mediated cytokine secretion, acute phase protein production, and cytochrome P450 suppression (Hoebe et al, 2001;Sunman et al, 2004;Nguyen et al, 2015;Sarkar et al, 2015;Rose et al, 2016). There are other mechanisms mediated by IL-6 that could potentially be modeled in the LiverChip system such as drug transporter activity.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor exists in both a cell membrane-bound form and a shed soluble form (sIL-6R), both of which bind IL-6 with equivalent affinity and mediate the same downstream signaling cascade (Rose-John, 2012;Scheller et al, 2014). C-reactive protein (CRP), an acute phase protein secreted by hepatocytes in response to IL-6, is commonly used as an in vitro marker of IL-6 signaling in hepatocytes (Bode et al, 2012;Nguyen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%